(untitled) (Journal of Economic Research & Business Administration, 2016)
This paper examines the distribution of the national budget cost by functional groups and budget programs, comparative evaluation of their changes. On the basis of forecast data are studied the amount and structure of costs by years of three-year budgets for 2015-2017 and 2016-2018, the tendencies and directions of financing the budget programs, as well as set the volume ratio of the forecast of financing from various budget programs. Some of the factors and conditions of changes in the approved budget were identified, which justified the changes and additions that are made each year to the tax legislation, as well as inefficient and inappropriate use of budget programs administrators of budget funds allocated, which also worsen the state budget planning. There also operate at a higher cost of the state related to its acquisition of financial assets, becouse the cost, ultimately, increase the budget deficit.